Mind the gap: The health advantages that accompany parental marriage vary by maternal nativity. (2nd September 2019) - Sigle, Wendy; Goisis, Alice
Abstract : Using data from the UK Millennium Cohort Study (MCS), we examine whether and how the health benefits of having two biological parents in a continuous marital relationship vary by maternal nativity and ethnicity, comparing UK-born White mothers with: (1) White mothers born in wealthy countries; (2) ethnic minority mothers from South Asia; and (3) ethnic minority mothers born in Africa. Making novel use of classification and regression tree (CART) methods, we examine whether marital status is a uniform marker of economic advantage or better health-related behaviours across the four maternal nativity and ethnic groups. The findings, which indicate that the health-related advantages associated with parental marriage are not uniform across the four nativity and ethnic groups, have implications for future research on family gaps in well-being and the socio-economic determinants of health.